Public Health Leadership during COVID-19 Pandemic: A Systemic Review - Gary Goh Chun Chao; Khairul Nizam Anwar; Mohd Hafizuddin Ahmad; Priya Dharishini Kunasagran; Sheila Miriam Binti Mujin; Zaharuddin Bujang; Abdul Rahman Ramdzan; Aniza Ismail; Aidalina Mahmud (ResearchGate, 2023)
Introduction: Nations around the world have enacted strict lockdowns due to COVID-19 pandemic and in order to alter and eliminate inadequacies in the public health care system, leaders’ passion, vision, and influence are essential. This review aims to explore the role of public health leadership during the COVID-19 pandemic. Methods: PRISMA was used to report this review and article regarding leadership during the COVID-19 pandemic and published from March 2020 until December 2021 was selected. Scopus and PubMed database were used to search the articles. Result: There were 29 articles in the review that focused on the three main competencies which were adaptive, people and task. The findings of this review demonstrate how critical public health leadership effectively handling crisis like the COVID-19 pandemic. Conclusion: Therefore, all countries should invest on the development of these competencies among their public health specialists. Newer leadership strategies, competencies, styles, and qualities need to be researched upon and adopted accordingly.